2022
DOI: 10.1021/acs.jafc.2c05228
|View full text |Cite
|
Sign up to set email alerts
|

Bitter Peptides YFYPEL, VAPFPEVF, and YQEPVLGPVRGPFPIIV, Released during Gastric Digestion of Casein, Stimulate Mechanisms of Gastric Acid Secretion via Bitter Taste Receptors TAS2R16 and TAS2R38

Abstract: Eating satiating, protein-rich foods is one of the key aspects of modern diet, although a bitter off-taste often limits the application of some proteins and protein hydrolysates, especially in processed foods. Previous studies of our group demonstrated that bitter-tasting food constituents, such as caffeine, stimulate mechanisms of gastric acid secretion as a signal of gastric satiation and a key process of gastric protein digestion via activation of bitter taste receptors (TAS2Rs). Here, we tried to elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
(102 reference statements)
0
13
0
Order By: Relevance
“… a Note: index 0–9 is derived from Liang’s work, index 10–12 is derived from Richter’s work, index 13–21 is derived from Liu’s work, index 22–29 is derived from Shan’s work, index 30–38 is derived from Zhang’s work, index 39–47 is derived from Liang’s work, and index 48–53 is derived from Cui’s work …”
Section: Resultsmentioning
confidence: 99%
“… a Note: index 0–9 is derived from Liang’s work, index 10–12 is derived from Richter’s work, index 13–21 is derived from Liu’s work, index 22–29 is derived from Shan’s work, index 30–38 is derived from Zhang’s work, index 39–47 is derived from Liang’s work, and index 48–53 is derived from Cui’s work …”
Section: Resultsmentioning
confidence: 99%
“…However, our current research is mainly based on in vitro cell antioxidant experiments to study the antioxidant activity of the Se-enriched peptides. Considering the possible changes in the structure of these Se-enriched peptides during digestion and the metabolic transformation after absorption, the relevant effective concentrations obtained in the current experimental results need to be further verified in animal or human intervention studies.miaojy8181@scau.edu.cn…”
Section: Resultsmentioning
confidence: 99%
“…Several indole derivatives have been found in bitter cruciferous vegetables, such as broccoli, cabbage, and Brussels sprouts . Although not related to sensory bitter taste perception, Ritcher et al recently reported bitter peptides upregulated the gene expression of TAS2R16 and TAS2R38, which altered gastric acid secretion from HGT-1 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Identified Amino Acid Sequence of a Bitter PA1b Variant Peptide in PPI in bitter cruciferous vegetables, such as broccoli, cabbage, and Brussels sprouts. 32 Although not related to sensory bitter taste perception, Ritcher et al 33 recently reported bitter peptides upregulated the gene expression of TAS2R16 and TAS2R38, which altered gastric acid secretion from HGT-1 cells. Furthermore, the PA1b peptide is known to possess an inhibitor cysteine knot (ICK) or knottin motif, where the two disulfide bonds form a loop through which the third disulfide bond passes.…”
Section: Sample Evaluation and Known Bitter Compoundmentioning
confidence: 99%